Ayude a proteger áreas naturales de Florida contra la invasión de plantas exóticas - Kenneth A. Langeland (EDIS, 2008)
Circular 1204-Sp, an 8-page illustrated  publication by K.A. Langeland, is the Spanish language version of Circular 1204, “Help Protect Florida’s Natural Areas from Non-Native Invasive Plants.” It describes the problem of weeds in natural areas, federal and state laws regulating plants, official lists of non-native invasive species. It encourages Florida residents to learn to identify invasive plants and to remove them from their property. Includes references. Published by the UF Department of Agronomy, February 2008.